2015
DOI: 10.5120/20316-2375
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study for Optimum Design of Grid Connected PV System based on Actual System Specifications

Abstract: This paper presents a comparative study using new approach for optimum design of rooftop grid connected PV system installation on an institutional building at Minia University, Egypt. The new approach demonstrated in this paper based on optimal configuration of PV modules along with inverters according to not only MPP voltage range but also maximum DC input currents of the inverter. Five different brands of commercially available PV modules and inverters have been conducted in this study. Many different config… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…During solar PV plants working, there are negligible of carbon dioxide emissions gas. Saving amount of CO2 emission can be evaluated using the equation (Hassan & Elbaset, 2015):…”
Section: Environmental Effect Of Photovoltaic Technologymentioning
confidence: 99%
“…During solar PV plants working, there are negligible of carbon dioxide emissions gas. Saving amount of CO2 emission can be evaluated using the equation (Hassan & Elbaset, 2015):…”
Section: Environmental Effect Of Photovoltaic Technologymentioning
confidence: 99%
“…The performance ratio of both systems remained consistently between 0.74 and 0.85, with an annual energy yield of approximately 1642.5 kWh/kWp. (Hassan & Elbaset, 2015) also conducted an evaluation of a grid-connected photovoltaic system installed on the rooftop of Minia University in Egypt, assessing its energy output and conducting a techno-economic analysis. The evaluation of grid-connected photovoltaic (PV) systems at the Hashemite University in Jordan was demonstrated by (Hammad et al, 2017) .The yearly energy output of two PV systems with and without tracking components, each with a capacity of 7.98 kWp, amounted to 2572 kWh/kWp and 1959 kWh/kWp, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies can be found in the literature which investigate the energy performance, cost assessments and environmental impact of different PV grid connected systems. Studies may be found in literature for countries with climate near to climate of Iraq like in Kuwait [9,10], Jordan [11], Egypt [12], Saudi Arabia [13], Turkey [14], Oman [15] and United of Arabian Emirates [16]. A detailed summary for the recent studies involving grid tied PV system with or without battery storage are reported in literature [15].…”
Section: Introductionmentioning
confidence: 99%